2021
DOI: 10.24815/jipi.v5i4.23446
|View full text |Cite
|
Sign up to set email alerts
|

Studi Profil Literasi Sains Siswa dan Pembelajarannya di SMP Kota Banda Aceh

Abstract: Descriptive research on the study of the scientific literacy profile of students and their learning at SMP Kota Banda Aceh, aims to examine the extent to which aspects of scientific literacy according to PISA 2018 are internalized in the junior high school science learning process. In addition, this study also examines its impact on students' scientific literacy. Research data to reveal the emergence of aspects of scientific literacy in planning learning, implementation of learning, and evaluation of learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Questions are tested on students to measure scientific literacy skills using the Test of Scientific Literacy Skills (TOSLS) instrument. The low results of scientific literacy are in line with the findings of Kamil (2022) who measures scientific literacy in Banda Aceh City Junior High School. The learning profile at Banda Aceh City Junior High School does not have continuity between learning planning and the learning process and evaluation carried out.…”
Section: Resultssupporting
confidence: 81%
“…Questions are tested on students to measure scientific literacy skills using the Test of Scientific Literacy Skills (TOSLS) instrument. The low results of scientific literacy are in line with the findings of Kamil (2022) who measures scientific literacy in Banda Aceh City Junior High School. The learning profile at Banda Aceh City Junior High School does not have continuity between learning planning and the learning process and evaluation carried out.…”
Section: Resultssupporting
confidence: 81%
“…Students are unable to relate scientific knowledge to phenomena that occur in the world (Fuadi et al, 2020). The reason for the low scientific literacy of students in Aceh is that teachers do not understand the characteristics of scientific literacy, how to design and implement science learning oriented towards increasing scientific literacy, as well as teachers' difficulties in designing scientific literacy assessments (Kamil et al, 2021). Teacher competence in developing creative thinking skills-oriented scientific literacy questions needs to be improved so that teachers can design and use these assessments and familiarize students with scientific literacy questions.…”
Section: Discussionmentioning
confidence: 99%
“…The average Indonesian student achieves level 2 or higher in science (OECD average: 78%). Several studies that identified students' scientific literacy skills in Aceh also found that students' scientific literacy skills were still categorized at a low level (Kamil et al, 2021;Dwisetiarezi & Fitria, 2021;Suparya et al, 2022). The reason for the low scientific literacy of students in Aceh is that teachers do not understand the characteristics of scientific literacy, how to design and implement science learning oriented towards increasing scientific literacy, as well as teachers' difficulties in designing scientific literacy assessments (Kamil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The types of PISA questions at level 2 are about simple experimental designs. Students can use contextual knowledge and build knowledge systematically to find solutions scientifically, analyze data, and identify topics to be solved (Kamil et al, 2021). Thus the need to increase literacy skills for Indonesian students who are still low (Kemendikbud, 2019).…”
Section: Introductionmentioning
confidence: 99%